Enantioselective organocatalytic diels-alder reactions: a density functional theory and kinetic isotope effects study - Omar, N.Y.M.; Zain, Sharifuddin Md; Rahman, N.A. (2011)
The mechanism and enantioselectivity of the organocatalytic Diels-Alder reaction were computationally investigated by density functional theory at the B3LYP/6-31G(d) level of theory. The uncatalyzed Diels-Alder reaction was also studied to explore the effect of the organocatalyst on this reaction in terms of energetics, selectivity, and mechanism. The catalyzed reaction showed improved endo/exo selectivity, and the free energy of activation was significantly lowered in the presence of the catalyst. Both uncatalyzed and catalyzed reactions exhibited concerted asynchronous reaction mechanism with the degree of asynchronicity being more evident in the presence of the catalyst. The Corey's experimentally derived predictive selection rules for the outcome of the organocatalytic Diels-Alder reaction were also theoretically analyzed, and an excellent agreement was found between experiment and theory. © 2011 Wiley Periodicals, Inc.